Multilevel Approach for Cryptography using Genetic Algorithms with Existing S-DES Key Generation Method - Pooja Bagane; Deepak Dharrao; S. Kotrappa (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Cryptography is the art of writing secret codes. Cryptographers try to write secret codes. Cryptanalysts will break secret codes. Cryptographers and cryptanalysts always try to be ahead of each other. Genetic algorithms (GA) are structured yet randomized search algorithm invented by Darwinian’s evolutionary ideas about natural selection and genetics. The field of security is colossal and vast. Many researchers are working in this field to achieve security and privacy. Researchers tried different evolutionary algorithms for cryptography. This paper discussed the multilevel approach for Cryptography using the S-DES Key Generation method and genetic algorithm. Convergence of S-DES and Genetic Algorithm is more secure and unbreakable than traditional cryptosystem.